A numerical modelling investigation of the development of a human cough jet. Issue 2 (13th July 2021) - Bi, Ran; Ali, Shady; Savory, Eric; Zhang, Chao
Abstract : Purpose: This study aims (1) to numerically investigate the characteristics of a human cough jet in a quiescent environment, such as the variation with time of the velocity field, streamwise jet penetration and maximum jet width. Two different turbulence modelling approaches, the unsteady Reynolds-averaged Navier–Stokes (URANS) and large eddy simulation (LES), are used for comparison purposes. (2) To validate the numerical results with the experimental data. Design/methodology/approach: Two different approaches, the URANS and LES, are used to simulate a human cough jet flow. The numerical results for the velocity magnitude contours and the spatial average of the two-dimensional velocity magnitude over the corresponding particle image velocimetry (PIV) field of view are compared with the relevant PIV measurements. Similarly, the numerical results for the streamwise velocity component at the hot-wire probe location are compared with the hot-wire anemometry (HWA) measurements. Furthermore, the numerical results for the streamwise jet penetration are compared with the data from the previous experimental work. Findings: Based on the comparison with the URANS approach and the experimental data, the LES approach can predict the temporal development of a human cough jet reasonably well. In addition, the maximum width of the cough jet is found to grow practically linearly with time in the far-field, interrupted-jet stage, while the corresponding axial distance from the mouth of the jet front increases with time in an approximately quadratic manner. Originality/value: Currently, no numerical study of human cough flow has been conducted using the LES approach due to the following challenges: (1) the computational cost is much higher than that of the URANS approach; (2) it is difficult to specify the turbulent fluctuations at the mouth for the cough jet properly; (3) it is necessary to define the appropriate conditions for the droplets to obtain statistically valid results. Therefore, this work fills this research gap.